Innovative startups in Italy. Managerial challenges of knowledge spillovers effects on employment generation. Issue 10 (12th October 2020) - Barboza, Gustavo; Capocchi, Alessandro
Abstract : Purpose: This paper aims to investigate the impact of knowledge spillover effects (KSE) on employment levels using a sample of 245 Italian Innovative startup companies created as a result of the legislative changes of Law Decree 179/12 introduced in Italy in 2012. Design/methodology/approach: This study uses a parsimonious model with the employment level as the dependent variable. The paper tests for the impact that the measures of industry competition, specialization and diversity have on the level of employment in the Innovative Startup sector in Italy. The data uses a sample of 245 firms, across 20 geographic regions in Italy for three economic sectors at the 2-Dig NAICS classification. Findings: The empirical results provide evidence in favor of regional specialization as the main force to create and transfer knowledge resulting in increased employment; while higher levels of competition and a more diverse regional production bases result in lower firm employment levels. Employment levels for these firms are also time-dependent, and thus mainly determined at the time of the firm's creation. This study also found a lack of technological convergence across regions, that are inherent regional differences are not bridged by knowledge spillover effects. Research limitations/implications: This paper is based on a sample of Italian Innovative Startups and consequently, further research with a potentially larger sample and, perhaps, a sample across countries could also shed some light on the issues relating to KSE and their effects on employment generation and firm formation. Practical implications: From a practical point of view, the results indicate that regional disparity and limited transmission of KSE across regions remain an impediment to the flow of knowledge. This in turn may limit the development of entrepreneurial activities and further development of new firms. Practical implications regarding knowledge management indicate that firms face time and spatial challenges when developing, transferring and acquiring knowledge. In sum, the evidence points out in favor of existent and persistent regional heterogeneity in terms of economic and technological specialization as sources of employment. Originality/value: This research adds to the empirical evidence focusing on the effects of knowledge spillover effects in the Innovative Startup segment of the economy. This research highlights the applicability of knowledge spillover effects accounting for levels of industry competition, specialization and diversity. We also provide a measure of cluster formation and concentration at the sectoral and regional levels. Thus, the research provides a better understanding under which conditions knowledge is more likely to have positive or negative effects on employment generation.